Al Ghazali's thoughts of economic growth theory, a contribution with system thinking - Irijanto, Tubagus Thresna; Zaidi, Mohd Azlan Shah; Ismail, Abdul Ghafar; Che Arshad, Noraziah (Indonesia Student Association from Universiti Kebangsaan Malaysia (National University of Malaysia) Bangi, Selangor Darul Ehsan, Malaysia., 2015)
This article tried to view ideas and economic thought of Al Ghazali, which had these thoughts tend to separate, in the sense that these thoughts as not to form an understanding of the aggregate economy. this is why the paper tries to explore and analyze further the thoughts and ideas of Al-Ghazali in the framework of the system, especially in terms of building a theory of economic growth.Modeling with Systems Thinking is used to facilitate the analysis and establish a model of economic growth of Al Ghazali, which is expected to be produced more comprehensive understanding of the thoughts and ideas of the Al Ghazali.